Optimalisasi Sistem Pengolahan Air Limbah Domestik Berbasis Biofilter Anaerob-Aerob di Permukiman Padat Penduduk - Putri, Riska Adianti; Julianti, Salbiah (Journal of Science and Technology: Alpha, 2025)
The rapid expansion of densely populated urban settlements poses significant challenges in managing domestic wastewater. Traditional treatment systems often operate inefficiently, resulting in environmental pollution and heightened public health risks. This study seeks to evaluate and optimize a domestic wastewater treatment system utilizing an anaerobic-aerobic biofilter, offering an effective and sustainable solution for high-density residential areas. The methodology involves designing and implementing a two-stage biofilter reactor: the first stage facilitates the anaerobic decomposition of complex organic compounds, while the second stage employs aerobic processes to oxidize residual organic matter. The results demonstrate that the system effectively reduces BOD, COD, and TSS levels by approximately 80%, 75%, and 85%, respectively, while maintaining stable performance under varying organic load conditions. Moreover, the system presents notable advantages, including space efficiency, low operational costs, and ease of maintenance, making it particularly well-suited for densely populated environments. Optimization efforts focused on adjusting the hydraulic retention time, refining the distribution of biofilter media, and incorporating passive aeration systems to enhance energy efficiency. In conclusion, the anaerobic-aerobic biofilter system represents an effective, environmentally sustainable, and practical alternative for community-scale wastewater treatment in urban areas.